Enhancing tumor-specific uptake of the anticancer drug cisplatin with a copper chelator - Ishida, Seiko (2010)
Uptake of the anticancer drug cisplatin is mediated by the copper transporter Ctr1 in cultured cells. Here we show in human ovarian tumors that low levels of Ctr1 mRNA are associated with poor clinical response to platinum-based therapy. Using a mouse model of human cervical cancer, we demonstrate that combined treatment with a copper chelator and cisplatin increases cisplatin-DNA adduct levels in cancerous but not in normal tissues, impairs angiogenesis, and improves therapeutic efficacy. The copper chelator also enhances the killing of cultured human cervical and ovarian cancer cells with cisplatin. Our results identify the copper transporter as a therapeutic target, which can be manipulated with copper chelating drugs to selectively enhance the benefits of platinum-containing chemotherapeutic agents.